Effect of Spray Drying Conditions on Physical Properties of Panax notoginseng Saponin (PNS) Powder and the Intra-Batch Dissolution Variability of PNS Hydrophilic Matrix Tablet - Yang M; Xu B; Wang X; Li W; Cao J; Li W; Qiao Y (Drug Design, Development and Therapy, 2021)
Maorui Yang,1 Bing Xu,1,2 Xin Wang,1 Wanting Li,1 Junjie Cao,1 Wenjing Li,1 Yanjiang Qiao1,2 1Department of Chinese Medicine Informatics, Beijing University of Chinese Medicine, Beijing, People’s Republic of China; 2Beijing Key Laboratory of Chinese Medicine Manufacturing Process Control and Quality Evaluation, Beijing, People’s Republic of ChinaCorrespondence: Bing Xu; Yanjiang QiaoDepartment of Chinese Medicine Informatics, Beijing University of Chinese Medicine, No. 11, North Third Ring East Road, Beijing City, 100029, People’s Republic of ChinaEmail xubing@bucm.edu.cn; yjqiao@bucm.edu.cnPurpose: Understanding raw material variability and its impact on product quality are crucial for developing robust pharmaceutical processes. This work aimed to study the effects of spray drying conditions on properties of the spray dried Panax notoginseng saponin (PNS) powders as well as the subsequent intra-batch dissolution variability of PNS hydrophilic matrix tablets.Methods: The Plackett-Burman design was applied to screen the critical process parameters (CPPs). Then, the Box-Behnken design was used to investigate the relationship between the CPPs and the physiochemical properties of spray dried PNS powders. The PNS hydrophilic matrix tablets containing 57% spray dried PNS powders were directly compressed. The partial least squares (PLS) regression was used to uncover the hidden multivariate relationships among the CPPs, intermediate powder properties, and tablet quality attributes.Results: The identified CPPs were the feed concentration, the inlet air temperature, and the atomization pressure. It was found that the CPPs exerted little impact on chemical properties of spray dried PNS powders, but had significant impact on physical properties, such as particle size, specific surface area, bulk density, hygroscopicity, and inter-particle porosity, etc. Latent variable modeling results revealed that the high inlet air temperature of spray drying process could produce PNS powders with low moisture content and high hygroscopicity, which were beneficial to reduce the intra-batch dissolution variability of PNS hydrophilic matrix tablets. Finally, a design space of the spray drying process was built in order to ensure the dissolution consistency.Conclusion: Our research provided a reference for improving the spray drying conditions in order to ensure the dissolution consistency of the PNS hydrophilic matrix tablet.Keywords: spray drying, Panax notoginseng saponin, hydrophilic matrix tablet, dissolution variability, quality by design